An Empirical Evaluation of the Link between Women Participation in Village Savings and Loans Association (VSLA) and Poverty Reduction in Ethiopia - Beyene, Nardos Legesse; Dinbabo, Mulugeta F. (Journal of Reviews on Global Economics, 2019)
Women's participation is a fundamental prerequisite for gender equality and genuine democracy. It facilitates women's direct engagement in decision-making and is a means of ensuring better accountability to women. This paper assesses the impact of women participation in Village Savings and Loans Association (VSLA) on poverty reduction in Hawassa city, Ethiopia. Using a mixed research methodology, and applying propensity score matching, the study found that women participation in VSLA has a significant positive impact in increasing average monthly household income of participant woman. Besides, women participation in VSLA has a significant positive association with improvements in household diet, health, children's education, and women's involvement in household decisions. The study recommends a reinforcement of government and nongovernmental organizations in providing regular and need based capacity building trainings for VSLA participants followed by a concerted effort to link VSLA participants with formal microfinance institutions.